IMPLEMENTASI PENGAJIAN HALAQAH DALAM MEMBENTUK AKHLAK PESERTA DIDIK MELALUI PENGAJIAN KITAB KUNING DI MADRASAH AS’ADIYAH PUSAT SENGKANG KABUPATEN WAJO - Marjuni, H. Andi; Iqbal, Muhammad (Inspiratif Pendidikan, 2022)
Halaqah has been started since the beginning of Islam. As is known, Mecca is the center of religion for the Arabs. There is the worship of the Kaaba and the worship of idols and idols which are sanctified by the entire Arab nation. The aspiration to improve the condition of the Arabs is certainly more difficult and difficult if the people who want to make improvements are far from the state of the Arab nation's environment. This requires a lot of effort so, in the face of such conditions, the wisest course of action is not to be surprised to suddenly encounter something that irritates the Arabs. halaqah as a teaching and learning process carried out by students, by circling the teacher concerned. Usually sits on the floor and continues to listen to a teacher read and explain his book or comment on the work of others. Halaqah can be interpreted as teaching and learning activities carried out by a cleric or kiai by sitting in front of his students while reading book material. The students who follow this learning system, sit in a semi-circle. In such a position, at the beginning of learning, the method used is the lecture method, then it is varied with other methods, such as the guidance method. The Ustad or Kiai guides the reading of the students while providing corrections when there is an inappropriate reading of the students. The Ustad or Kiai also explains the contents of the book in words or sentences in Arabic, Indonesian, or other languages ​​if needed.